2014
DOI: 10.3390/nu6114839
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Proliferative Effects of Enterolactone in Prostate Cancer Cells: Evidence for the Role of DNA Licencing Genes, mi-R106b Cluster Expression, and PTEN Dosage

Abstract: The mammalian lignan, enterolactone, has been shown to reduce the proliferation of the earlier stages of prostate cancer at physiological concentrations in vitro. However, efficacy in the later stages of the disease occurs at concentrations difficult to achieve through dietary modification. We have therefore investigated what concentration(s) of enterolactone can restrict proliferation in multiple stages of prostate cancer using an in vitro model system of prostate disease. We determined that enterolactone at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 46 publications
1
14
1
Order By: Relevance
“…31 Both in vitro and clinical studies have suggested that a diet rich in precursors of mammalian lignans (e.g., whole grain rye, bran or flaxseed) may have antiproliferative effects in the early stages of prostate cancer development. [37][38][39] However, findings from the current study do not support the hypothesis that circulating lignans play a role in the aetiology of prostate cancer.…”
Section: Discussioncontrasting
confidence: 99%
“…31 Both in vitro and clinical studies have suggested that a diet rich in precursors of mammalian lignans (e.g., whole grain rye, bran or flaxseed) may have antiproliferative effects in the early stages of prostate cancer development. [37][38][39] However, findings from the current study do not support the hypothesis that circulating lignans play a role in the aetiology of prostate cancer.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, miR‐1825, which was also downregulated by resveratrol in our study, was recently shown to be promising as a potential urinary miRNA biomarker candidate for the detection of prostate cancer among benign prostatic hyperplasia patients . Remarkably, miR‐106b, which was downregulated by resveratrol in our microarray studies and was validated functionally, was found to be compellingly oncogenic in nine available prostate cancer reports . Studies validated the functional involvement of miR‐106b in regulation of genes encoding important cancer‐related proteins, such as PTEN, REST, E2F1, p21, and CASP7 .…”
Section: Role Of Resveratrol‐ and Resveratrol Analog–regulated Mirnassupporting
confidence: 74%
“…Studies validated the functional involvement of miR‐106b in regulation of genes encoding important cancer‐related proteins, such as PTEN, REST, E2F1, p21, and CASP7 . In addition, changes in miR‐106b levels have been reported in response to metformin, enterolactone, and radiation . However, the role of several resveratrol‐regulated miRNAs that have been implicated in prostate cancer pathophysiology is controversial.…”
Section: Role Of Resveratrol‐ and Resveratrol Analog–regulated Mirnasmentioning
confidence: 95%
“…The plant is rich in carvacrol, a phenolic monoterpene with recognized anti-inflammatory and antitumor properties (Burts & al. 2007;McCann & al. 2014).…”
Section: Introductionmentioning
confidence: 99%